The Effects of Loan-to-Value (LTV), Minimum Reserve Requirement (MRR), and Capital Adequacy Ratio (Car) on the Performance of State-Owned Banks - Ananta, Dimas; Rahmadana, Muhammad Fitri; Fitrawaty, Fitrawaty (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the impact of macroprudential policies on The Performance of State-Owned Banks in Indonesia, focusing on Loan to Value (LTV), Minimum Reserve Requirement (MRR), and Capital Adequacy Ratio (CAR). The research is motivated by the need to understand how macroprudential instruments influence the financial performance of major banks amid evolving credit, liquidity, and capital conditions. The problems addressed are whether LTV, MRR, and CAR individually and collectively affect Return on Equity (ROE), and which of these variables serve as the most influential determinants of profitability. The study aims to analyze the partial and simultaneous effects of these indicators on ROE using empirical data from four large Indonesian banks over the 2013–2023 period. The research employs a panel data regression approach using the fixed-effect model to estimate the relationships among variables. The empirical results show that LTV has a negative and significant effect on ROE, indicating that looser LTV policies tend to reduce profitability through increased credit risk. MRR has a positive but insignificant effect, suggesting that reserve requirements primarily function as liquidity buffers rather than direct profitability drivers. CAR exhibits a positive and significant effect, highlighting the importance of strong capitalization in supporting bank performance. Simultaneously, LTV, MRR, and CAR significantly influence ROE, with an R-squared value of 0.2723, meaning that 27.23% of variation in profitability is explained by these macroprudential indicators. Overall, the findings underscore the essential role of integrated macroprudential policy in maintaining bank performance and financial stability.